THE BASIC PSYCHOLOGICAL NEEDS IN THE ENGLISH SUBJECT: A RASCH MEASUREMENT MODEL - Susanto, Alpino; Megah S, Suswanto Ismedi; Susanti, Ervin Nora (Asosiasi dosen IDEBAHASA KEPRI, 2023)
A matter of great interest to researchers in the field of education today is how to improve students' well-being, engagement, or learning achievement in tertiary level contexts. Some scholars suggest to start from the assessment of students' satisfaction upon their basic psychological needs. However, recently, the number of validated tools to assess the satisfaction of the basic psychological needs is still rare. This study measured the validity and reliability of an adapted basic psychological needs theory used in foreign language learning. There were two developed questionnaires to identify basic psychological needs which covers a different number of indicators. The study presented empirical evidence of validity and reliability using the Rasch Model. This pilot study was conducted in two different universities and cities, Indonesia. There were 34 students as a participant in this study. Data were analyzed using WINSTEPS version 3.69.1.11. Results show that the instrument that can measure BPN in the context of English courses at the tertiary level is feasible to use in measuring BPN. The researchers only got one invalid item from the